Drivers of increased organic carbon concentrations in stream water following forest disturbance: Separating effects of changes in flow pathways and soil warming. Issue 4 (24th December 2013) - Schelker, J.; Grabs, T.; Bishop, K.; Laudon, H.
Abstract [1] Forest disturbance such as clear‐cutting has been identified as an important factor for increasing dissolved organic carbon (DOC) concentrations in boreal streams. We used a long‐term data set of soil temperature, soil moisture, shallow groundwater (GW) levels, and stream DOC concentrations from three boreal first‐order streams to investigate mechanisms causing these increases. Clear‐cutting was found to alter soil conditions with warmer and wetter soils during summer. The application of a riparian flow concentration integration model (RIM) explained a major part of variation in stream [DOC] arising from changing flow pathways in riparian soils during the pretreatment period (r2 = 0.4–0.7), but less well after the harvest. Model residuals were sensitive to changes in soil temperature. The linear regression models for the temperature dependence of [DOC] in soils were not different in the disturbed and undisturbed catchments, whereas a nonlinear response to soil moisture was found. Overall these results suggest that the increased DOC mobilization after forest disturbance is caused by (i) increased GW levels leading to increased water fluxes in shallow flow path in riparian soils and (ii) increased soil temperature increasing the DOC availability in soils during summer. These relationships indicate that the mechanisms of DOC mobilization after forest disturbance are not different to those of undisturbed catchments, but that catchment soils respond to the higher hydro‐climatic variation observed after clear‐cutting. This highlights the sensitivity of boreal streams to changes in the energy and water balance, which may be altered as a result of both land management and climate change.